A Comparative Analysis of Management of Dairy Animals under Organic and Non-organic Farming System in Uttarakhand: Calf Rearing and Mortality Perspective: Comparative Analysis of Management of Dairy Calves under Organic and Non-organic Farming System - Maji, Saikat; B S Meena; Neela Madhav Patnaik (Indian Journal of Dairy Science, 2024)
Dairy farming provides livelihood and nutritional security to the vast majority families throughout rural India. In this livelihood system dairy calves play a very important role as most of the farming families carefully raise the young calves to become efficient producer in terms of milk or as a source of drought power. For organic farmers the necessity of proper calf management assumes more importance due to restriction on diet choice and also due to more stress on welfare-based animal rearing.  In this context, present study was undertaken in Uttarakhand, one of the leading states in organic farming, as a part of larger study on dairy based organic farming. 240 farmers (120 both organic and non-organic farmers) were surveyed, compulsorily having either cattle, buffalo or goat as dairy animal or any combinations of these enterprises. Calf management practices were studied from the context of recommended practices of organic farmers.  It was found that variation existed between organic and non-organic farmers in plain and hilly region and also for different species of dairy animals. Keeping the calf separately with respective mother was most common practice at least for few days after birth. Mutilation practices like castration was higher in hilly region irrespective of farming system especially for cattle than in buffalo. Disbudding was also practiced by many organic farmers in violation of organic standards. Under miscellaneous management practices colostrum feeding after birth was found to be followed by all organic and farmers in plain and hilly regions. Also, the paper shed some light on varied probability (increasing or decreasing) of practicing/compliance to various calf management practices if farmers moved from non-organic to organic farming. The calf mortality pattern between organic and non-organic management was not found to be significantly different.